Rwanda : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper for Rwanda reports the growth strategy described in the Poverty Reduction Strategy Paper (PRSP). The PRSP constitutes a critical effort aimed at generating poverty-reducing economic growth. Sustained growth in the primary sector serves as an engine of growth in the rural nontradable sector. The consequent rural employment generation provides income to the poorest among the rural poor. In generating an annual rural nonfarm growth rate of 6.7 percent, the PRSP assumes an elasticity of rural nonfarm activities with respect to farm growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet